Olfactory sensitivity to catecholamines and their metabolites in the goldfish - Hubbard, Peter (2014)
The current study assessed the olfactory sensitivity of the goldfish (Carassius auratus L.) to the catecholamines, their immediate precursors and metabolites by use of the electro-olfactogram (EOG). The olfactory system of the goldfish was found to be sensitive to both adrenaline and dopamine with thresholds of detection of 10–7.8 and 10–7.9 M respectively, but less so to noradrenaline (threshold of detection 10–6.3 M). The 3-O-methoxy metabolites (metadrenaline, normetadrenaline and 3-O-methoxytyramine) evoked larger amplitude EOGs than the non-metabolized form with lower thresholds of detection. However, the olfactory system was less sensitive to the amino acid precursors L-tyrosine and L-DOPA, and markedly less so to the α-deaminated metabolites (3,4-dihydroxyphenyl glycol, 3,4-dihydroxy mandelic acid and dihydroxyphenyacetic acid). Sensitivity to metabolites, both α-deaminated and 3-O-methoxylated, was similar to the α-deaminated forms. Crossadaptation studies suggested that, while there is some degree of commonality of the receptor mechanisms with L-tyrosine and L-serine, a proportion of the response to the catecholamines is due to distinct receptor subtypes. Similarly, the 3-O-methoxy metabolites also had (a) separate receptor mechanism(s), although, again, there was overlap with the adrenaline/dopamine receptor site(s). Presence of the α-adrenoreceptor antagonist prazosin or the peripheral DA2 dopamine receptor antagonist domperidone caused partial attenuation of the EOG responses to adrenaline and dopamine, but had much less effect on the responses to their 3-O-methoxy metabolites. The β-adrenoreceptor antagonist sotalol had no such effect. This suggests that the olfactory catecholamine receptors are structurally and functionally distinct from systemic adreno- and dopamine receptors. The current study raises the possibility that release of catecholamines or their 3-O-methoxy metabolites to the water may play a role in chemical communication.